Respiratory Function and Information Processing Speed in Coal Power Plant Workers: Moderating Effects of Physical Activity and Sedentary Behavior - Kim PS; Lai TF; Park JH; Jang M; Shin YK; Kim DR; Wang IJ; Choi HJ; Lee JI (Risk Management and Healthcare Policy)
Pill Soo Kim,1,2 Ting-Fu Lai,2,3 Jong-Hwan Park,4– 6 Minwoo Jang,2 Yeo-Kyung Shin,2 Du-Ri Kim,2 Il Jae Wang,2,7 Hyuk Jin Choi,1,2,8 Jae-Il Lee1,2,8 1Department of Neurosurgery, Pusan National University Hospital, Busan, Republic of Korea; 2Biomedical Research Institute, Pusan National University Hospital, Busan, Republic of Korea; 3Graduate Institute of Sport, Leisure and Hospitality Management, National Taiwan Normal University, Taipei City, 106, Taiwan; 4Department of Convergence Medicine, Pusan National University School of Medicine, Yangsan, Republic of Korea; 5Department of Clinical Bio-Convergence, Graduate School of Convergence in Biomedical Science, Pusan National University School of Medicine, Yangsan, Republic of Korea; 6Convergence Medical Institute of Technology, Pusan National University Hospital, Busan, Republic of Korea; 7Department of Emergency Medicine, Pusan National University School of Medicine, Yangsan, Republic of Korea; 8Department of Neurosurgery, Pusan National University School of Medicine, Yangsan, Republic of KoreaCorrespondence: Jae-Il Lee, Email medifirst@pusan.ac.krBackground: In occupational settings like coal power plants, impaired respiratory function and cognitive performance can pose significant risks to worker safety and productivity. This study aimed to investigate the associations between respiratory muscle strength and information processing speed in coal power plant workers, and to explore whether these associations are moderated by physical activity and sedentary behavior.Methods: A cross-sectional study was conducted among 171 coal power plant workers. Respiratory muscle strength was assessed using Maximal Inspiratory Pressure (MIP) and Peak Expiratory Flow (PEF). Information processing speed was evaluated using a validated tablet-based cognitive assessment tool. Physical activity levels and sedentary behavior were assessed using the International Physical Activity Questionnaire (IPAQ). Multiple linear regression analyses were performed to examine the associations between respiratory function and cognitive performance, stratified by physical activity levels and sedentary behavior patterns.Results: After adjusting for covariates, in the active group (≥ 150 min/week of moderate-to-vigorous physical activity), individuals with MIP < 80% showed significantly lower information processing speed scores (B = − 6.341, 95% CI: − 11.709 to − 0.972, p = 0.021) compared to those with MIP ≥ 80%. Similarly, those with PEF < 80% demonstrated significantly lower scores (B = − 8.383, 95% CI: − 14.601 to − 2.165, p = 0.009). In the non-prolonged sedentary group (< 9 hours/day), participants with MIP < 80% exhibited significantly lower scores (B = − 6.655, 95% CI: − 11.684 to − 1.626, p = 0.010). No significant associations were observed in the inactive or prolonged sedentary groups.Conclusion: The relationship between respiratory muscle strength and information processing speed in coal power plant workers is moderated by physical activity levels and sedentary behavior patterns. These findings highlight the importance of considering occupational factors in health interventions and suggest that promoting physical activity and reducing sedentary time could have multifaceted benefits for this workforce.Keywords: Respiratory function, cognitive performance, coal power plant workers, physical activity, sedentary behavior, occupational health, occupational exposure